(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Preterm birth is an essentially rising global problem, however more than 60% of those occur in South Asia and Sub-Saharan Africa. The present study was conducted to compare oral and vaginal natural micronised progesterone 300 mg in preventing preterm labor. Materials & Methods: 80 pregnant women with gestational age between >24 week to <36 weekswere divided into 2 groups of 40 each. Group I patients were administered oral micronized progesterone 300 mg and group II were administered vaginal micronized progesterone. APGAR scoreat 5 minutes and birthweight were recorded. Number of neonates who required NICU admission were noted. Results: Gestational age 24-28 weeks had 10 patients in group I and 12 in group II, 29-32 weeks had 24 in group I and 20 in group II and 32-36 weeks had 6 in group I and 8 in group II. Perinatal outcome was asymptomatic at birth seen in 30 and 34, meconium aspiration syndrome in 1 and 2, birth asphyxia in 5 and 1, neonatal sepsis in 2 and 1 and hypoxemic ischaemic encephalopathyin 2 and 1 in group I and II respectively. The difference was significant (P< 0.05).NICU admission was seen in 4 in group I and 2 in group II, APGAR score at 1 minute was 7.25 in group I and 8.15 in group II and at 5 minutes was 7.85 in group I and 8.69 in group II. The mean birth weight<2.5 kgs was seen in 11 and 4, 2.5-3 Kgs in 15 and 11 and >3 kgs in 14 and 25 in group I and II respectively. The difference was significant (P< 0.05).Conclusion: Vaginal mode of administration is considered more efficaciousas compared to oral progesterone. It plays a vital role in the reduction of pre- term labor, reduces the rate of neonatal NICU admissions, neonatal mortality and morbidity.